Neurogenin-2 induced neuronal differentiation in co-cultured bone marrow stromal and neonatal cortical cells - Saba Majeed,; Aisha Aziz,; Kanwal Iftikhar,; Shabana Usman Simjee, (Journal of the Pakistan Medical Association, 2024)
Objective: To explore a novel and dynamic role for neurogenin-2 in promoting cortical neurogenesis in cells produced from co-culturing neonatal cortical neural progenitor cells with bone marrow stromal cells. Method: The experimental study was conducted from June 2016 to January 2019 at the neuropharmacology laboratory of the Hussein Ebrahim Jamal Research Institute of Chemistry, International Centre for Chemical and Biological Sciences, Karachi. The growth of cells at different stages in harvested cells was determined by 3-(4, 5- dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay. Immunocytochemistry was used to evaluate the protein expressions of neuronal markers and transcription factors. Data was analysed using SPSS 20. Results: Data showed significant generation of neuronal cells and this was also verified by increased expression of nesting in cortical co-cultures with bone marrow stromal cells. Immunoreactive outcomes showed over expressions in co-cultured chlorotoxin cells. Subsequently, neurogenin-2 was found intermixed with induced expressions of transcriptional factor NeuroD1 and reduced glial fibrillary acidic protein-labelled cells. Conclusion: Better understanding of the mechanisms underlying transcriptional modulation of neurogenic events hold the key for emerging treatment approaches towards neurodegeneration. Key Words: Coculture, Glial Fibrillary, Bromides, Immunohistochemistry, Chlorotoxin, diphenyl, Neuropharmacology, Mesenchymal, Neurogenesis, Stem Cells.